Comparison of sucrose and human milk on pain response in newborns - SAVE, DİLŞAD; ÖZEK, EREN; BİLGEN, HÜLYA SELVA (SPRINGER VERLAG, 1999)
The aim of this study was to compare the analgesic effect of 2 ml 25% sucrose and human milk in a group of healthy term newborns. Healthy infants (n = 102) were randomly allocated to receive one of three solutions (sucrose, human milk: sterile water) 2 min prior to taking a heel prick blood sample. The median values of crying time, recovery time and percentage change in heart rate at 1, 2 and 3 min were recorded in response to the heel prick. Median crying times were 36, 52, and 62 s in the sucrose, placebo and human milk groups, respectively (P = 0.0009). In the sucrose group, there was a significant reduction in crying time compared to human milk and placebo groups. Similarly, the median recovery time in the sucrose group (72 s) was shorter than that in the human milk (112 s) and placebo groups (124 s) (P 0.004). The percentage change in heart rate at 1, 2 and 3 min was also significantly lower in the sucrose group (P = 0.008, P = 0.01, P = 0.002 at 1, 2, and 3 min respectively). Conclusion The orosensorial antinociceptive effect of human milk is not as effective as an analgesic as a 25% sucrose solution.
Keywords: analgesia; newborn; sucrose; milk; PRETERM INFANTS; TERM INFANTS; HEEL PRICK; HYPOALGESIA; ANALGESIA; GLUCOSE; TASTE; RATS